The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41588-018-0048-5
|View full text |Cite
|
Sign up to set email alerts
|

CLCN2 chloride channel mutations in familial hyperaldosteronism type II

Abstract: Primary aldosteronism, a common cause of severe hypertension1, features constitutive production of the adrenal steroid aldosterone. We analyzed a multiplex family with familial hyperaldosteronism type II (FH-II)2 and 80 additional probands with unsolved early-onset primary aldosteronism. Eight probands had novel heterozygous variants in CLCN2, including two de novo mutations and four independent occurrences of the identical p.Arg172Gln mutation; all relatives with early-onset primary aldosteronism carried the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
186
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(210 citation statements)
references
References 50 publications
5
186
1
8
Order By: Relevance
“…In a recent report of a family with FH type II and 80 additional probands with unsolved early onset PA, the authors found germline CLCN2 chloride channel mutations in eight of the probands [103]. All relatives with early onset PA carried the CLCN2 variant found in the proband.…”
Section: Fh Type I: Cyp11b1/cyp11b2 Germline Chimeric Genementioning
confidence: 96%
“…In a recent report of a family with FH type II and 80 additional probands with unsolved early onset PA, the authors found germline CLCN2 chloride channel mutations in eight of the probands [103]. All relatives with early onset PA carried the CLCN2 variant found in the proband.…”
Section: Fh Type I: Cyp11b1/cyp11b2 Germline Chimeric Genementioning
confidence: 96%
“…Criteria for the diagnosis of FH II are at least two first-degree members of the same family have confirmed PA and FH-I and familial hyperaldosteronism type-III (FH-III) have been excluded 76 . Six different mutations have been identified in CLCN2, encoding for a chloride channel, at conserved regions of the channel (p.M22K, p.G24D, p.Y26N, p.R172Q, p.delK362 and p.S865R) 77,78 . Mutation leads to open the channel and abolish the voltage dependency of the channel.…”
Section: Fh IImentioning
confidence: 99%
“…FH‐II is a not glucocorticoid remediable form of PA, traditionally considered as clinically and biochemically indistinguishable from a sporadic form . The genetic basis of some of the families affected by FH‐II has been very recently identified in germline mutations in the CLCN2 gene, encoding for the chloride channel ClC‐2, which is expressed in adrenal zona glomerulosa . The reported mutations facilitate the channel opening at the zona‐glomerulosa resting potential, resulting in cell membrane depolarization and up‐regulation of CYP11B2 expression .…”
Section: Primary Aldosteronismmentioning
confidence: 99%
“…53,54 The reported mutations facilitate the channel opening at the zona-glomerulosa resting potential, resulting in cell membrane depolarization and up-regulation of CYP11B2 expression. 53,54 The mode of transmission is autosomal dominant with incomplete penetrance. 54 Further studies are warranted to establish the impact (in term of prevalence) of CLCN2 mutations in FH.…”
Section: Familial Primary Aldosteronismmentioning
confidence: 99%
See 1 more Smart Citation